Context‐dependent effects of yolk androgens on nestling growth and immune function in a multibrooded passerine. (1st July 2015) - Muriel, J.; Salmón, P.; Nunez‐Buiza, A.; de Salas, F.; Pérez‐Rodríguez, L.; Puerta, M.; Gil, D.
Abstract Female birds may adjust their offspring phenotype to the specific requirements of the environment by differential allocation of physiologically active substances into yolks, such as androgens. Yolk androgens have been shown to accelerate embryonic development, growth rate and competitive ability of nestlings, but they can also entail immunological costs. The balance between costs and benefits of androgen allocation is expected to depend on nestling environment. We tested this hypothesis in a multibrooded passerine, the spotless starling, Sturnus unicolor. We experimentally manipulated yolk androgen levels using a between‐brood design and evaluated its effects on nestling development, survival and immune function. Both in first and replacement broods, the embryonic development period was shorter for androgen‐treated chicks than controls, but there were no differences in second broods. In replacement broods, androgen‐treated chicks were heavier and larger than those hatched from control eggs, but this effect was not observed in the other breeding attempts. Androgen exposure reduced survival with respect to controls only in second broods. Regarding immune function, we detected nonsignificant trends for androgen treatment to activate two important components of innate and adaptive immunity (IL‐6 and Ig‐A levels, respectively). Similarly, androgen‐treated chicks showed greater lymphocyte proliferation than controls in the first brood and an opposite trend in the second brood. Our results indicate that yolk androgen effects on nestling development and immunity depend on the environmental conditions of each breeding attempt. Variation in maternal androgen allocation to eggs could be explained as the result of context‐dependent optimal strategies to maximize offspring fitness.